Stability of Orally Dissolving Film of Zingiber officinale Roscoe Extract With HPMC And Maltodextrin as Polymer - Srie Rezeki Nur Endah; Iis Nur Asiah; Susanti Susanti; Nitya Nurul Fadilah; Ali Nofriyaldi (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
The pharmaceutical industry is developing pharmaceutical technology with better bioavailability because the drugs are absorbed pre-gastric, namely orally dissolving film (ODF). The ODFs containing HPMC as a film-forming agent exhibit brittleness, stickiness, and a rough surface. In contrast, maltodextrin polymer-based films have a smooth transparent surface, tensile strength, and mouthfeel. Testing the effect of varying concentrations of maltodextrin as a film-forming agent on the characterization of ODF. Three formulas with different ratio of HPMC and maltodextrin polymer (2:1; 2:2; 2:3) were tested for organoleptic, film thickness, pH, folding endurance, disintegration, and stability of the ODF. The test results were then analyzed statistically using the one-way analysis method. Formulas 1, 2, and 3 reduce the characteristics of ODF red ginger extract in the form of a thin yellow-brown layer with a distinctive odor and spicy taste, a film thickness of 0,06-0,10 mm, a ph of 6,82-6,92, a folding endurance of 368-418x fold, and a disintegration of 48,59-61,39 seconds. Variations in the concentration of maltodextrin as a polymer show that there is an influence on the characteristics of the ODF red ginger extract, which is indicated by a sig value of <0,05 in testing a film thickness, pH, folding endurance, and disintegration.